The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2023
DOI: 10.1002/jtr.2579
|View full text |Cite
|
Sign up to set email alerts
|

Is travel bragging in the eye of the beholder? Bragger and audience perspectives

Abstract: Travel bragging refers to showing off or boasting about travel experiences. Despite its ubiquity on social media, travel bragging has been relatively under‐researched. This study examines travel bragging from a dual perspective of both braggers and audiences. Based on 30 semi‐structured interviews with participants who frequently posted or bragged about travel experiences and who had been frequently exposed to others' travel bragging on social media, we provide the first systematic conceptualization of travel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 51 publications
0
0
0
Order By: Relevance
“…They are usually, but not always aspirational in nature (Xu et al, 2016), often producing bragging rights through experiencing the best, unique or amazing places (Liu et al, 2023). Indeed, Liu et al (2019) concluded that when positive travel experiences were shared with peer group members, people with lower self-esteem showed a stronger desire to visit places offering a luxury travel experience.…”
Section: Ideal or Dream Vacationsmentioning
confidence: 99%
“…They are usually, but not always aspirational in nature (Xu et al, 2016), often producing bragging rights through experiencing the best, unique or amazing places (Liu et al, 2023). Indeed, Liu et al (2019) concluded that when positive travel experiences were shared with peer group members, people with lower self-esteem showed a stronger desire to visit places offering a luxury travel experience.…”
Section: Ideal or Dream Vacationsmentioning
confidence: 99%